(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides detailed information about the specific features of the post-doctoral education system of the Finnish state, the stages of the academic career after the doctorate (post doctorate) educational system. As well as, some suggestions and comments were made regarding the application of some acceptable aspects of the education system of the Finnish state to the education system of our country.